A systematic review approach to technologies used for learning and education. (2015) - Purarjomandlangrudi, Afrooz; Chen, David; Nguyen, Anne
E-learning is implementation of technologies in learning process and is growing at a very rapid pace. E-learning technology has matured noticeably and the majority of organisations are taking advantage of it in their educational systems. However, there is a lack of methodical and consistent paradigm of these technologies in literature. The purpose of this study is to conduct a systematic literature review on past research regarding application of technologies in education to propose a structured and taxonomic classification for technologies used in learning and education to shed a light on the way of their users. Reviewed studies were excluded on the basis of their title, abstract and full text to arrive at a final set of 343. The result of data analysis is nine main categories of technologies. A summary of implications and conclusions of the research analysis are also provided for both industry practitioners and researchers to take advantage of them.